Investigating the Validity Evidence of the Swedish TriPM in High Security Prisoners Using the PCL-R and NEO-FFI - Pauli, Malin; Ölund Alonso, Hannibal; Liljeberg, Jenny; Gustavsson, Petter; Howner, Katarina (Frontiers in Psychiatry, 2021)
The triarchic model of psychopathy was developed to bridge opposing descriptions of psychopathy by separating the core construct in three domains; boldness, meanness and disinhibition. The Triarchic Psychopathy Measure (TriPM) operationalizes the model through a 58-item self-report questionnaire. The current study examined the psychometric properties of the Swedish translation by investigating intercorrelations and associations to expert-rated psychopathy, general personality and psychopathy-related traits in male high-security prisoners (n = 191). Psychopathy rated with TriPM and the Psychopathy Checklist Revised (PCL-R) demonstrated expected convergence, as did empathy and impulsivity measures. The Disinhibition and Meanness scales were highly correlated, indicating that the scales might not be adequately differentiated. Nevertheless, the divergent association patterns to other important variables, particularly neuroticism and empathy, also points to meaningful differences. However, the lack of association between Disinhibition and Boldness may put into question if these domains are related at all, especially since there was a lack of similarity in the association patterns with other clinical variables. The influence of antisocial behavior in the TriPM operationalization might amplify the similarities of the Meanness and Disinhibition scales, while diluting the associations between Meanness and Boldness. In conclusion, the Swedish TriPM is effective in measuring the domains of triarchic model in forensic settings, even though a revision of the scales might improve the psychometric properties of the instrument.